Practical and scientific experiences from optimizing the sport-specific development of endurance transfer athletes - Talsnes, R. K.; Hetland, T.-A.; Sandbakk, O. (Nordic Winter Sports Conference, 2020)
Aiming for cross-country (XC) skiing success at the 2022 Beijing Winter Olympics, China has developed a talent transfer program where endurance athletes from different summer sports (e.g. running, rowing and kayaking) have been transferred to XC skiing by utilizing Norwegian coaching and training methods. In this presentation, we will 1) describe how we coached and systematically monitored these athletes in order to optimize their performance-development and 2) show scientific data describing the factors underlying successful talent transfer in XC skiing.